Performance Analysis of Pongamia (Karanj Oil) as Fuel in Diesel Engine - Srinivasan, V.; Loganathan, G.; Luther King, M. Francis; Kumar, G. (International Journal of Psychosocial Rehabilitation, 2019)
The experimental outcomes on a diesel engine with numerous emission performances of fuels primarily based on Ppongamia pinnata oil as compared with diesel gasoline. Fuels utilized in experimental research have been combinations of Pongamia pinnata methyl ester and diesel in exclusive proportions: 80% diesel—20% PPME, 60% diesel—40% PPME, 40% diesel—60% PPME, 20% diesel gas—80% PPME, 100% PPME, and 100% diesel as a reference. The project had focused on the use of fuels derived from Ppongamia pinnata oil on the prevailing Kirloskar AV1 engines. Fuel-related properties were reviewed and compared with the ones of traditional diesel fuel. The effect of use of biofuel on engine emissions from biodiesel and diesel fuels was as compared, paying unique interest to the maximum enormous emissions, which include hydrocarbons, carbon monoxide, nitric oxides, and particulates.